2013
DOI: 10.1186/bcr3442
|View full text |Cite
|
Sign up to set email alerts
|

Elevated expression of syntenin in breast cancer is correlated with lymph node metastasis and poor patient survival

Abstract: IntroductionSyntenin is a scaffolding-PDZ domain-containing protein. Although it is reported that syntenin is associated with melanoma growth and metastasis, the possible role of syntenin in breast cancer has not been well elucidated. The present study investigated the expression and function of syntenin in breast cancer.MethodsReal-time polymerase chain reaction (PCR) and Western blots were used to determine the mRNA and protein expression of syntenin. With a combination of overexpression and RNA interference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 36 publications
4
50
0
Order By: Relevance
“…egFR belongs to the erbB proto-oncogene receptors family (erbB tyrosine kinase receptors), and its cognate ligand has been considered as a common component of various cancer types to induce tumor growth (23,24). EGFR overexpression has been confirmed in multiple carcinomas including breast cancer, urothelial cell carcinoma and hepatoma (10,16). It is believed that egFR can trigger a cascade of multiple signaling pathways to regulate cancer cell proliferation, maintenance, invasion, metastasis, survival and prognosis (16,17,25,26).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…egFR belongs to the erbB proto-oncogene receptors family (erbB tyrosine kinase receptors), and its cognate ligand has been considered as a common component of various cancer types to induce tumor growth (23,24). EGFR overexpression has been confirmed in multiple carcinomas including breast cancer, urothelial cell carcinoma and hepatoma (10,16). It is believed that egFR can trigger a cascade of multiple signaling pathways to regulate cancer cell proliferation, maintenance, invasion, metastasis, survival and prognosis (16,17,25,26).…”
Section: Discussionmentioning
confidence: 99%
“…As a PDZ domain-containing molecule, syntenin can exert multiple roles and regulate diverse and central physiologic processes (8,9). The function of syntenin in cancer has attracted increasing attention for its important roles in the development of various cancers, including melanoma, breast and bladder cancer (10,12,13). It has been confirmed that syntenin is highly expressed in several cancer cells and tissues, and it is involved in the progression of cancer, including cancer cell growth, invasion and metastasis (9,21,22).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations